Dronning Maud Land: der ingen skulle tru at det var fjell ... - Engeland, Sveinung; Engeland, Sveinung (Høyde over havet : hvordan fjellene våre ble målt og satt på kartet, 2021)
Keywords: Dronning Maud Land; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

På tokt i Dronning Maud Land - Steen, Harald ("Kronprins Haakon", 2020)
Keywords: Sørishavet; ekspedisjoner; marinbiologi

Sett fra luften - Berg, Thomas Reinertsen (Verdensteater : kartenes historie, 2017)
Keywords: ekspedisjoner; flyfotografering; karthistorie; kartlegging; kartografi

"Big Science" for meteorologene - Nilsen, Yngve; Vollset, Magnus (Vinden dreier : meteorologiens historie i Norge, 2016)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi

Frozen voices: Women, silence and Antarctica - Blackadder, Jesse (Antarctica : music, sounds and cultural connections, 2015)
This chapter explores a different kind of Antarctic silence: the silencing of certain stories and voices. It’s the silence of the earliest female travellers to Antarctica.The voices of the earliest female travellers are silent and their stories remain untold, partly because there’s no place for them in the dominant Antarctic narrative of exploration and conquest. Reimagining them through fiction is one way — though with potential pitfalls — to ‘unfreeze’ those stories.
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

The Third Expedition, 1910-1912: Antarctica and the Southern Ocean - Johnson, Charles W (Ice ship : the epic voyages of the polar adventurer Fram, 2014)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Sydpolen - Skog, Cecilie; Sandberg, Sigri (Cecilie Skog og de tre polene, 2006)
Keywords: Antarktis; Sydpolen; Sørpolen; biografi; ekspedisjoner; reiser; reiseskildringer

Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

Den første norske oljealderen - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Sørishavet; ekspedisjoner; hvalfangstindustri; hvalolje; pelagisk

Polarheltene - minner og monumenter - Eriksen, Anne (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; polarfarere; polarområdene

Å spise kirsebær med de store - Friedman, Robert Marc (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; oppdagelsesreiser

"En æressag for vor nation" - Fulsås, Narve (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser

Kappløp i gamle spor - Goksøyr, Matti (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; ekspedisjoner

Klodens helse - sett fra polene - Hessen, Dag O (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; ekspedisjoner; forskning; internasjonalt samarbeid

Christensen, Lars - Mills, William J (Exploring polar frontiers : a historical encyclopedia, 2003)
Keywords: Antarktis; biografier; ekspedisjoner; hvalfangst; polarhistorie; polfarere

Joint marine project during NARE 200/01: dissolved oxygen and nutrient tracers in the marine Norwegian sector of the Antarctic - Fransson, Agneta; Nøst, Ole Anders; Olsson, Kristina; O'Dwyer, Jane; Drange, Helge; Børsheim, Knut Yngve; Gammelsrød, Tor; Søreide, Janne; Karlsen, Tor Ivan; Jensen, Glen (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; biogeokjemi; ekspedisjoner; marin biologi; oseanografi

Antarctica - Sale, Richard (Polar reaches : the history of Arctic and Antarctic exploration, 2002)
Keywords: Antarktis; Sydpol; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; hvalfangere; oppdagelsesreiser; polarområdene

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Scott und Amundsen - Barr, Susan (Arktis Antarktis, 1997)
Keywords: Antarktis; ekspedisjoner; historie

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Geodetic measurements at Vestfjella and Heimefrontfjella - Barstad, Bjørn; Luktvasslimo, Brit Åse (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; ekspedisjoner; geodesi; satellittbilder; topografi

Detailed studies of bottom freezing under an iceshelf and mapping of accumulation by use of multi-frequency pulse-aperture radar - Erlingsson, Bjørn; Gjessing, Yngvar; Hamran, Svein Erik; Holmlund, Per (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; ekspedisjoner; georadar; isshelf; topografi

Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

The Norwegian-British-Swedish Antarctic expedition 1949-1952 - Liljequist, Gösta H (High latitudes : a history of Swedish polar travels and research, 1993)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Adaptations to alpine and polar environments in insects and other terrestrial arthropods - Sømme, Lauritz; Block, William (Insects at low temperature, 1991)
Keywords: Antarktis; ekspedisjoner; insekter; kuldetoleranse; polarområdene; virvelløse dyr

Geological observations in Gjelsvikfjella and Mühling-Hofmannfjella - Bucher-Nurminen, Kurt; Ohta, Yoshihide; Austrheim, Håkon; Dallmann, Winfried K (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geologi

Geodetic measurements in Dronning Maud Land - Eiken, Trond; Luktvasslimo, Brit Åse; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geodesi

Observations of ice shelf water at the southern Weddel sea shelf break - Foldvik, Arne; Gammelsrød, Tor; Nordlund, Nina; Nytun, Kjell (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isshelf; oseanografi

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Marine geological studies in the Weddel sea - Sjøholm, Jorunn; Jansen, Eystein (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; marin geologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi

Sydpolen 1910-1912 - Huntford, Roland; Hoff, Truls (Roald Amundsens oppdagelsesreiser i bilder, 1988)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Early geological exploration of Seymour Island, Antarctica - Zinsmeister, William J (Geology and Paleontology of Seymour Island, Antarctic Peninsula, 1988)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Seymourøya; Vestantarktis; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

General outline of the botanical investigations on Bouvetøya - Engelskjøn, Torstein (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Botany of Gjelsvikfjella and Muhlig-Hofmannfjella, Dronning Maud Land - Engelskjøn, Torstein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; planter

Swedish Antarctic research. A historical Review - Liljequist, Gösta H (Sweden and Antarctica, 1985)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; meteorologi

Terrestrial Habitats - invertebrates - Sømme, Lauritz (Antarctica, 1985)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

The mineral resources of Antarctica: progress in their identification - Gjelsvik, Tore (Antarctic Resources Policy: Scientific, Legal and Political Issues, 1983)
The increment in informationCareful geological investigations started at a few places in Antarctica after World War II, but gained momentum and became systematic only when the International Geophysical Year started, and when SCAR and its Working Group on Geology were established just 25 years ago. Although geology was not initially part of the IGY programme, it soon became one of the thriving sciences in Antarctica.The growth of Antarctic geosciences can be shown in many ways, for example by the expansion of the Symposium volumes from the first one in 1963, containing 76 papers, to the latest one in August 1982, with 191 papers.The investigations have largely had the character of regional reconnaissance surveys, and the observations have mostly been published as general descriptions with maps at the scale of 1:1 million or smaller. Only one Antarctic nation has a systematic mapping programme of larger scales (1:500,000). In a few cases, such as in areas around some larger stations, more detailed work has been going on, in some cases also related to mineral occurrences. A few programmes are under way that have aspects of being resource-oriented: investigations of the Dufek Massif, a layered intrusion similar to the Cr-, Pt- and Ni-rich Bushfeld complex in South Africa, and sampling of manganese nodules during marine geological surveys. Airborne radiometric surveys and also some marine seismic surveys conducted by national oil companies or by resource-oriented state agencies belong to this category.
Keywords: Antarktis; ekspedisjoner; forskning; geologi; mineraler; ressurser

Marine geophysical research in the Weddell Sea during the Norwegian Antarctic research expedition of 1976-77 - Fossum, Bjørn A.; Maisey, Georg H.; Torsen, Hans Olav (Antarctic geoscience : Symposium on Antarctic Geology and Geophysics, Madison, Wisconsin, U.S.A., August 22-27, 1977, 1982)
Paper No. 45
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; geologi; marin geofysikk

The geology, volcanic activity, and age of Bouvetøya, South Atlantic - Prestvik, Tore (Norwegian Antarctic Research Expeditions (1978/79), 1982)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi; vulkaner

Analysis of wave measurements at Bouvetøya - Arntsen, Øivind A; Snuggerud, John (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; ekspedisjoner; forskning; oseanografi

Terrestrial vegetation of Bouvetøya : a preliminary account - Engelskjøn, Torstein (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; botanikk; ekspedisjoner; forskning

An eruptional model for recent lava flow on Bouvetøya, South Atlantic Ocean - Furnes, Harald; Løvlie, Reidar (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner

Stratigraphy and igneous petrology of Southern Heritage Range, Ellsworth Mountains, Antarctica - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S (Results from Norwegian Antarctic Research 1974-1977, 1978)
Sedimentary and magmatic rocks of Late Proterozoic to Late Paleozoic age, from the southern half of Ellsworth Mountains are described. Basic volcanic rocks, mainly agglomeratic, occur abundantly in the lower part of the succession, in the Minaret Group, and in the lower part of the Heritage Group, but are not recorded in the upper part of the Heritage Group. Due to this lithostratigraphic contrast a new classification is proposed: the Heritage Group including the Middle Horseshoe Formation and the Edson Hills Formation. A stratigraphic gap is evident above the Edson Hills Formation and a separate unit–the Dunbar Ridge Formation–is proposed. This formation is of Middle-Upper Cambrian age, with trilobite-bearing limestones. The structure is governed by a major anticline with a NW plunge in the north but almost horizontal in the south. Contrast of fold intensity and fold style below the youngest exposed unit, the Whiteout Conglomerate and a weathered surface above the Crashite Quartzite suggests a late Paleozoic deformation phase. Two phases of magmatism are distinguished. The pre-Middle Cambrian magmatism is dominantly K-alkalic and suggests the beginning of block subsidence at the early stage of a rift tectonics on a continental crust. The presumptive Late Paleozoic magmatism is N-alkalic and tholeiitic, and occurred after the main deformation; however the rocks were regionally metamorphosed in the actinolite-greenschist facies probably in late Paleozoic time. This magmatism is considered to represent an advanced stage of block tectonics. (Auth. mod.)
Keywords: Antarktis; ekspedisjoner; geologi; petrologi; stratigrafi; vulkaner

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi

Weather and tide observations at Bouvetøya - Vinje, Torgny E (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi; observasjoner; oseanografi

Observations on birds and seals at Bouvetøya - Fevolden, Svein Erik; Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Bouvetøya; ekspedisjoner; fugler; pingviner; zoologi

Sydpolen - Mountfield, David; Sollie, Finn (De store polaroppdagelser, 1977)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Antarktis - Antonsen, Per (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ekspedisjoner; polarområdene

Hva gjør Norge i Antarktis? - Orheim, Olav (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ekspedisjoner; forskning; politikk

Some observations on the geology of H. U. Sverdrupfjella, Dronning Maud Land - Hjelle, Audun (Norsk Polarinstitutt. Årbok 1972, 1974)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; stratigrafi

The South Pole - Mountfield, David (A history of polar exploration, 1974)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

Byrd's South Pole Flight - 1929-30 - Isakson, Evelyn Moore (Bernt Balchen, colonel, United states Air force, retired : a special report on the unique career of a great American patriot, 1972)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Upper wind - Robin, Gordon de Quetteville; Hisdal, Vidar; Hisdal, Vidar (Meteorology I, 1971)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; meteorologi

Sealing and seal research in the south-west Atlantic pack ice, Sept.-Oct. 1964 - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: MV Polarhav; Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Norske oppdagelser og rettigheter i Antarktis. Vurdering av norske territoriale og andre rettigheter i Arktis og Antarktis (En oversikt over fiske, fangst og norske polarinteresser, 1967)
Keywords: Antarktis; Bouvetøya; Norge; ekspedisjoner; fiske; hvalfangere; hvalfangst; interesser; internasjonal; oppdagelsesreiser; politikk

Tredje etappe av Dronning Maud Land Traversen - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1967, 1967)
Keywords: Antarktis; ekspedisjoner; meteorologi; observasjoner

What is "Mumiyo" from Antarctica - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1967, 1967)
Keywords: Dronning Maud Land; ekspedisjoner; farmakologi; fugler; ornitologi; zoologi

Fra Sydpolen til "Utilgjengelighetens pol" (From The South Pole to The Pole of Inaccessibility) - Dybvadskog, Olav (Norsk Polarinstitutt. Årbok 1964, 1966)
Keywords: Antarktis; ekspedisjoner; forskning; glasiologi; gravimetri; meteorologi; observasjoner; seismologi

Annen etappe av Dronning Maud Land Traversen - Orheim, Olav (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; glasiologi; gravimetri; meteorologi; seismologi

Besøk på Bouvetøya i 1958 og 1966 (Bouvetøya twice visited) - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Bouvetøya; ekspedisjoner; geologi; observasjoner; topografi

Christensen and Mawson - Grierson, John (Challenge to the poles : highlights of Arctic and Antarctic aviation, 1964)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; luftfart; oppdagelsesreiser

The Norwegian/British/Swedish Expedition to Queen Maud Land - Grierson, John (Challenge to the poles : highlights of Arctic and Antarctic aviation, 1964)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; luftfart

The surface inversion - Hagen, K; Hisdal, Vidar (Meteorology I, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; meteorologi

The tropopause - Schumacher, Nils Jörgen; Hisdal, Vidar (Meteorology I, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; meteorologi

The cooling power in Antarctica - Vinje, Torgny E (Norsk Polarinstitutt. Årbok 1961, 1962)
We have measured the cooling power at Norway Station (70°.5 S, 2°.5 W)with kata-thermometers for air-temperature (Ta) between + 1 and –41° C, and for wind speeds (v) at 10 m leve! up to 27 m sec-1• The linear proportionality of the cooling power (H) to (36.5-Ta), for a constant wind speed, is shown to hold in this temperature-interval for a wind speed less than about 12 m sec-1• We used four kata-thermometers, and it turned out that they gave systematic different values of the cooling power for equal meteorological conditions. Comparing the individual values with their mean we find a maximum deviation of about ± 20 % . W e have supposed that this is due to errors in the calibration, subjective errors plus dissimilarities in the shape of the bulbs. The latter will cause differences in the turbulence around the bulbs, and consequently in the effective cooling of the wind. The possible difference in the cooling power of the air due to differences in the shape will probably not emerge during calibrations in a still air chamber. In spite of the dissimilar climatic conditions in Antarctica and Europe we found that a formula based upon two of our Katas, with which we have taken by far the most measurements, corresponds fairly well to the mean of the Kata-formulae found in Europe. The maximum deviation of the values given by European formulae from those derived by the Norway Station formula is about ± 20 %. We have here omitted the formula of HILL (1919), as it reveals a fairly large deviation from the other formulae.
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; ekspedisjoner; meteorologi

Man in Antarctica - Rodahl, Kaare (Science in Antarctica. Part 1: The Life sciences in Antarctica, 1961)
Keywords: Antarktis; ekspedisjoner; forskning; fysiologi; kuldetoleranse; medisin; polarområdene

Temperature, height and humidity - Schumacher, Nils Jörgen; Hisdal, Vidar (Meteorology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; meteorologi

Narrative of the Expedition - Larsen, Nils (Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48, 1956)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ekspedisjoner; forskning; naturvitenskap; oseanografi; zoologi

The Norwegian Antarctic expedition in the "Brategg 1947-1948 - Mosby, Håkon (Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48, 1956)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ekspedisjoner; forskning; naturvitenskap; oseanografi; zoologi

Den norsk-britisk-svenske ekspedisjon til Antarktis 1949-52 - Giæver, John (Liv og virke ved polene, 1949)
Issue: 1949
Keywords: Dronning Maud Land; ekspedisjoner

Antarktiske ekspedisjoner i årene 1939-1949 - Werner-Johannessen, Thor (Liv og virke ved polene, 1949)
Issue: 1949
Keywords: Antarktis; ekspedisjoner; historie

Norske fangfstfolk og forskere i Antarktis. Den Tredje Framferda (1910-12). Mot Nordpolen via Sørpolen. Roald Amundsen planter den norske flagget på Sørpolen 14.-12.-1911 - Opsund, Enok (Nordmenn i polheimene, 1948)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; polarområdene

Hvalfangst på sydfeltet i krigstiden - Vikestad, Arne (Tusen norske skip : en antologi over norske sjøfolks innsats i den annen verdenskrig, 1948)
Keywords: Nordmenn; Sørishavet; Verdenskrigen 1939-45; ekspedisjoner; erindringer; hvalbåter; hvalfangst; pelagisk

Antarctic fishes - Nybelin, Orvar (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume II, 1947)
Keywords: Sørishavet; ekspedisjoner; fisker; forskning; zoologi

Antarctic and sub-antarctic birds - Holgersen, Holger (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume II, 1945)
Keywords: Bouvetøya; biologi; ekspedisjoner; fugler

Antarktische und subantarktische Polyplacophoren - Bergenhayn, Johan Richard Melin (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume II, 1937)
Keywords: Norvegia ekspedisjonen; Sørishavet; bløtdyr; ekspedisjoner; hydrografi; leddsnegler; marin biologi; zoologi

Wal und Walfischfang - Hjort, Johan (Polarbuch : neue Forschungsfahrten in Arktis und Antarktis mit Luftschiff, U-Boot, Schiffen und Forschungsschiff, 1933)
Keywords: Sørishavet; ekspedisjoner; hvalfangst; pelagisk

The South Pole attained: Amundsen in the Fram - Hayes, Gordon J (The conquest of the South Pole : antarctic exploration 1906-1931, 1932)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; polarområdene

The work of the whalers and the discovery committee - Hayes, Gordon J (The conquest of the South Pole : antarctic exploration 1906-1931, 1932)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; Odd I; ekspedisjonen; ekspedisjoner; forskning; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene

Exploring the great continent - Taylor, Griffith (Antarctic adventure and research, 1930)
Keywords: Antarktis; Carsten Borchgrevink; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

Kapitän Larsen auf "Jason" an der Ostküste der Westantarktis - Gerdes, Rudolf (Anteil der Deutschen an der Erforschung des Südpolargebietes, besonders der Westantarktis, bis zur internationalen Erforschung in den Jahren 1901-1903 : Beitrag zur Geschichte der Antarktis, 1917)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Seymourøya; Sørishavet; Vestantarktis; ekspedisjoner; hvalfangere; oppdagelsesreiser

Extracts from the Private Diary of the Late Nicolai Hanson - Hanson, Nicolai (Report on the collections of natural history made in the Antarctic regions during the voyage of the "Southern Cross", 1902)
Keywords: Antarktis; Kapp Adare; Rosshavet; Southern Cross; ekspedisjonen; ekspedisjoner; fauna; flora; fugler; oppdagelsesreiser; overvintring; seler; zoologi

The Voyage of the "Antarctic" to Victoria Land - Borchgrevink, Carsten Egeberg (Report of the Sixth International Geographical Congress. Held in London, 1895, 1896)
Keywords: Antarctic (skip); Antarktis; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Paa fangst i Sydishavet - Nielsen, Eivind (Sjømænd : norske Sjømænds Oplevelser : samlet fra Folkemunde og gjenfortalt, 1896)
Keywords: Carl Anton Larsen; Jason (skip); Sørishavet; ekspedisjoner; hvaler; hvalfangst; oppdagelsesreiser; pelagisk